PEMEROLEHAN KALIMAT BAHASA INDONESIA ANAK USIA EMPAT TAHUN DUA BULAN (4;2) (STUDI KASUS PADA SEORANG ANAK) - Gustanti, Nilda; Juita, Novia; Ngusman, Ngusman (Jurnal Bahasa dan Sastra, 2013)
This study was conducted to describe the following: (1) declarative sentence patterns children aged four years and two months, (2) the pattern of interrogative sentences children aged four years and two months, (3) pattern imperative sentence children aged four years and two months.This research is a qualitative study using descriptive methods. The data of this study is the pattern of declarative sentences, interrogative, and imperative children aged four years and two months. Data sources of this study is the speech act olds four years and two months. The methods used to collect the data of this study are proficient method, see, observations and supported by observation and recording techniques. The types of sentences in terms of the syntactic form be spoken by children ages 4;2 consists of sentences declarative, interrogative, and imperative. Declarative sentence patterns in terms of syntactic function be spokenÂ  children ages 4;2 which is the Subject (S), the Subject-Predicate (S-P), Predicate-Object (P-O), Predicate (P), Predicate-Subject (P-S), Subject-Predicate-Object (S-P-O), Subject-Predicate-Complement (S-P-Pel), Subject-Description (S-Ket) and Subject-Predicate-Deskription (S-P-Ket). Interrogative sentence patterns that be spokenÂ  children ages 4;2 is a pattern of what, who, when, where, why, and how. Imperative sentence patterns children ages 4;2 sent is to use patterns, encourage, hope, and banned.